Alternative substrates and controlled-release fertilizer in the production of yellow passion fruit seedlings - Braña Muniz, Paulo Sérgio; Andrade Neto, Romeu de Carvalho; Pereira Lunz, Aureny Maria; de Almeida, Ueliton Oliveira; de Araújo, James Maciel (Comunicata Scientiae, 2020)
There are many residues that can be used for agriculture, especially as a substrate. However, it is often necessary to fertilize the growing media so that the seedlings can be produced with quality. The objective of this study was to evaluate the use of alternative and commercial substrates associated with different controlled-release fertilizer levels in producing yellow passion fruit seedlings. The experiment was conducted at the Embrapa Acre seedling nursery, with 50% luminosity. We used a randomized block experimental design in a 5 x 3 factorial scheme with 15 treatments, 4 replicates, and 10 plants per plot. The treatments consisted of five controlled-release fertilizer levels (0 kg m-3, 3 kg m-3, 6 kg m-3, 9 kg m-3, and 12 kg m-3) combined with lumps of acerola fruits (LAF), Brazil nut peel (BNP), and commercial (CS) substrates. The evaluated variables were seed height, stem diameter, number of leaves, shoot dry mass (SDM), root dry mass (RDM), total dry mass (TDM), and seedling quality index (SQI). Use of the alternative lumps of acerola fruit (LAF) substrate associated with the 10 kg m-³ level of controlled-release fertilizer promoted the best results. BNP has potential for use as a substrate for passion fruit seedlings, however adjustments are necessary to achieve an adequate composition.